India-ASEAN Relation In The Framework Of Indo-Pacific - Abhiram Singh Yadav (Mandala: Jurnal Ilmu Hubungan Internasional, 2020)
Despite decades of successful implementation of multiple regional cooperation policies in East and Southeast Asia, the Indo-Pacific concept is yet to be institutionalized. This paper attempts to examine the challenges that face the institutionalization of the Indo-Pacific concept by focusing on previous foreign policies and their significance in the region. Based on the findings, recommendations are generated to reflect the way Indo-Pacific can successfully be institutionalized.